A novel twin‐column continuous chromatography approach for separation and enrichment of monoclonal antibody charge variants. Issue 6 (12th May 2021) - Jing, Shu‐Ying; Shi, Ce; Leong, Hui Yi; Yuan, Jun‐Jie; Gao, Dong; Wang, Hai‐Bin; Yao, Shan‐Jing; Lin, Dong‐Qiang
Abstract: Downstream processing of mAb charge variants is difficult owing to their similar molecular structures and surface charge properties. This study aimed to apply a novel twin‐column continuous chromatography (called N‐rich mode) to separate and enrich acidic variants of an IgG1 mAb. Besides, a comparison study with traditional scaled‐up batch‐mode cation exchange (CEX) chromatography was conducted. For the N‐rich process, two 3.93 mL columns were used, and the buffer system, flow rate and elution gradient slope were optimized. The results showed that 1.33 mg acidic variants with nearly 100% purity could be attained after a 22‐cycle accumulation. The yield was 86.21% with the productivity of 7.82 mg/L/h. On the other hand, for the batch CEX process, 4.15 mL column was first used to optimize the separation conditions, and then a scaled‐up column of 88.20 mL was used to separate 1.19 mg acidic variants with the purity of nearly 100%. The yield was 59.18% with the productivity of 7.78 mg/L/h. By comparing between the N‐rich and scaled‐up CEX processes, the results indicated that the N‐rich method displays a remarkable advantage on the product yield, i.e. 1.46‐fold increment without the loss of productivity and purity. Generally, twin‐column N‐rich continuous chromatography displays a high potential to enrich minor compounds with a higher yield, more flexibility and lower resin cost.